Effect of rotation of torque rheometer rotors on HDPE/UHMWPE blend mixture - Santos, Ryan Ferreira dos; Silva , Lucineide Balbino da (Seven Editora, 2023)
Seeking to evaluate the quality of polymeric blends when subjected to shear and temperature, the importance of the Torque Rheometer (RT) for the adjustment of process parameters is highlighted. That's because the Torque Rheometer (RT) is a state-of-the-art mixing and measuring system that focuses on specific research and development needs using small quantities of the sample (50g). The blends of high-density polyethylene (HDPE) and ultra-high molecular weight polyethylene (PEUAMM) were mixed at concentrations of 100/0, 90/10, and 70/30, all containing 0.5g or 1% of Irganox Antioxidant. The results were obtained from curves of torque as a function of time, which made it possible to evaluate the degradation of the blends during mixing, as well as the time to establish a homogeneous mixture. From the results obtained, it was observed that the blend of HDPE with 30% of PEUAMM composition in the rotation of 50 RPM presented a maximum torque as a function of time, being smaller than that of the blend of 10% of PEUAMM with the same rotation. The decrease in torque may have been due to molecular orientation since in the melt homogenization region (represented by the minimum torque) an increase in torque was observed over time. The addition of the thermal stabilizer may have avoided the thermal degradation of the 30% blend of PEUAMM for the 50 RPM rotation. Therefore, the mixing of HDPE/PEUAMM blends occurred without thermal degradation and with an indication of more difficult processability due to the increase in torque during the homogenization of the melt, with greater energy expenditure. DOI:https://doi.org/10.56238/devopinterscie-207